resin composition

JP2026169225APending Publication Date: 2026-10-16AJINOMOTO CO INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2026122431
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、粘度が高く、且つ、少ない露光量で光ファイバをシリコンチップの溝に接着させることが可能な樹脂組成物;並びに、その樹脂組成物を用いたデバイス及びその製造方法;を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169225000001_ABST
    Figure 2026169225000001_ABST
Patent Text Reader

Abstract

The present invention provides a resin composition that has high viscosity and can bond optical fibers to the grooves of a silicon tip with a small amount of exposure. [Solution] A resin composition for bonding optical fibers to grooves in a silicon chip; the resin composition comprises (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator; the resin composition may or may not contain (E) inorganic particles; and (E) the amount of inorganic particles is 15% by mass or less based on 100% by mass of the total amount of the resin composition.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a resin composition. More specifically, to a resin composition for bonding optical fibers to grooves in a silicon chip to which silicon photonics are applied; and to a device using the resin composition and a method for manufacturing the same. [Background technology]

[0002] Conventional optical semiconductor devices, in which optical components are mounted on a substrate, have sometimes been manufactured by bonding the optical components to the substrate using an adhesive. Patent Document 1 proposes using a photocurable adhesive composition as this adhesive. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2022-69039 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] Silicon is generally transparent at optical communication wavelengths of 1.1 μm or longer. Therefore, silicon photonics, which uses silicon to form optical integrated circuits, is attracting attention. In silicon photonics, it is possible to form fine optical waveguides on a silicon substrate using conventional LSI manufacturing techniques. For example, it is expected that silicon chips with nanometer-sized optical waveguides can be manufactured at low cost.

[0005] The aforementioned silicon chips formed using silicon photonics may require the connection of optical fibers. For example, to optically connect multiple silicon chips, it may be necessary to connect optical fibers to those silicon chips. Also, for example, silicon chips are expected to be mounted on an optoelectronic hybrid substrate. When multiple optoelectronic hybrid substrates are connected by optical fibers, it may be necessary to connect those optical fibers to silicon chips.

[0006] As a method for connecting optical fibers to silicon chips, the inventors focused on a connection method using grooves such as V-grooves and U-grooves. In this method, grooves for connecting optical fibers are formed on the surface of the silicon chip, and the optical fibers are bonded to these grooves using a photocurable adhesive. With this method, the position of the optical fiber can be precisely adjusted by using grooves.

[0007] Silicon chips using silicon photonics are currently in the research stage, and connection to optical fibers is mainly done manually. Therefore, for now, it is acceptable for the adhesive to take a long time to cure. However, in the future industrialization stage, high-speed mass production will be required, so it is expected that the adhesive will need to cure quickly. Specifically, the adhesive needs to be able to cure to a degree that provides sufficient adhesive strength with a small amount of exposure.

[0008] On the other hand, in optical fiber connections using grooves, the adhesive needs to have high viscosity in order to ensure uniform application of the adhesive. Specifically, the adhesive needs to have a viscosity of about 4 Pa·s or higher at room temperature (for example, 25°C).

[0009] However, when the resin composition used as an adhesive has high viscosity, the amount of exposure required for curing tends to increase. Therefore, there was a trade-off between increasing the viscosity of the resin composition and decreasing the amount of exposure required to promote curing. As a result, a resin composition that has high viscosity and can bond optical fibers to the grooves of silicon tips with a small amount of exposure has not yet been obtained.

[0010] The present invention was devised in view of the above-mentioned problems, and aims to provide a resin composition that has high viscosity and can bond optical fibers to grooves in silicon chips with a small amount of exposure; and a device using the resin composition and a method for manufacturing the same. [Means for solving the problem]

[0011] The inventors diligently studied to solve the aforementioned problems. As a result, the inventors found that a resin composition comprising (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator, wherein the amount of (E) inorganic particles in the resin composition is below a specific threshold, can solve the aforementioned problems, and thus completed the present invention. In other words, the present invention includes the following:

[0012] <1> A resin composition for bonding optical fibers to grooves in a silicon chip; The resin composition comprises (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator; The resin composition may or may not contain (E) inorganic particles; (E) A resin composition in which the amount of inorganic particles is 15% by mass or less relative to 100% by mass of the total amount of the resin composition. <2> (A) The amount of aliphatic liquid oxetane resin is 10 parts by mass or more and 50 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin. <1> The resin composition described above. <3> (B) The amount of aliphatic solid epoxy resin is 40 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin. <1> or <2> The resin composition described above. <4> (C) The amount of aliphatic liquid epoxy resin is 1 part by mass or more and 30 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin. <1> ~ <3> A resin composition according to any one of the items. <5> (D) The amount of photocationic polymerization initiator is 0.1 parts by mass or more and 5 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin. <1> ~ <4> A resin composition according to any one of the items. <6> (B) The aliphatic solid epoxy resin comprises one or more selected from the group consisting of hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a 6-membered ring. <1> ~ <5> A resin composition according to any one of the items. <7> (C) The aliphatic liquid epoxy resin comprises one or more selected from the group consisting of hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a 6-membered ring. <1> ~ <6> A resin composition according to any one of the items. <8> (E) The amount of inorganic particles is 0.1% by mass or less relative to 100% by mass of the total amount of the resin composition. <1> ~ <7> A resin composition according to any one of the items. <9> The process of installing optical fibers in the grooves of the silicon chip, In the groove, <1> ~ <8> A step of applying the resin composition described in any one of the items, A process for curing the resin composition, A method for manufacturing a device, including <10> A silicon tip with grooves formed on it, Optical fibers placed in the grooves of the silicon chip, It comprises an adhesive portion for bonding the optical fiber to the groove; The adhesive part, <1> ~ <8> A device comprising a cured product of a resin composition described in any one of the items. [Effects of the Invention]

[0013] The present invention provides a resin composition with high viscosity that allows optical fibers to be bonded to grooves in silicon chips with a small amount of exposure; as well as a device using the resin composition and a method for manufacturing the same. [Brief explanation of the drawing]

[0014] [Figure 1] Figure 1 is a schematic perspective view showing an optical device according to one embodiment of the present invention. [Figure 2] Figure 2 is a schematic cross-sectional view showing an optical device according to one embodiment of the present invention. [Figure 3] Figure 3 is a schematic perspective view showing a silicon chip included in an optical device according to one embodiment of the present invention. [Figure 4] Figure 4 is a schematic side view showing an example of two test tubes used to determine the liquid and solid states of a resin. [Modes for carrying out the invention]

[0015] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented without departing from the scope of the claims and their equivalents.

[0016] In the following explanation, the determination of whether a resin is liquid or solid will be made in accordance with the "Method for Confirming Liquidity" in Appendix 2 of the Ministerial Ordinance Concerning the Testing and Properties of Hazardous Materials (Ministry of Home Affairs Ordinance No. 1 of 1989). The specific determination method is as follows.

[0017] (1) Equipment Constant temperature water bath: The high-temperature water tank should be equipped with a stirrer, heater, thermometer, and automatic temperature controller (capable of controlling the temperature to within ±0.1°C), and should have a depth of 150 mm or more. For example, a low-temperature constant-temperature water bath (model BU300) manufactured by Yamato Scientific Co., Ltd. and an immersion-type constant-temperature device called Thermomate (model BF500) can be combined. Approximately 22 liters of tap water can be placed in the low-temperature constant-temperature water bath (model BU300), the power to the attached Thermomate (model BF500) can be turned on and set to the desired temperature, and the water temperature can be finely adjusted to within ±0.1°C of the set temperature using the Thermomate (model BF500). Alternatively, another device capable of similar adjustments can be used.

[0018] Test tube: Figure 4 is a schematic side view showing an example of two test tubes used to determine the liquid and solid states of a resin. As shown in Figure 4, the test tubes used are flat-bottomed cylindrical transparent glass test tubes with an inner diameter of 30 mm and a height of 120 mm, with markings 11A and 12B at heights of 55 mm and 85 mm from the bottom of the tube, respectively, and the mouth of the test tube sealed with a rubber stopper 13a. The test tube used for temperature measurement is of the same size and has markings in the same way, and the mouth of the test tube is sealed with a rubber stopper 13b with a hole in the center for inserting and supporting a thermometer, and a thermometer 14 is inserted into the rubber stopper 13b. Hereinafter, the marking at a height of 55 mm from the bottom of the tube will be referred to as "line A", and the marking at a height of 85 mm from the bottom of the tube will be referred to as "line B".

[0019] Thermometer 14 may be one specified in JIS B7410 (1982) "Glass thermometers for testing petroleum products" for measuring the freezing point (SOP-58 scale range 0°C to 100°C). Alternatively, another thermometer capable of measuring temperatures in the range of 0°C to 100°C may be used.

[0020] (2) Procedure for conducting the test The sample, left for 24 hours or more under atmospheric pressure at ±5°C of the set temperature, is poured into the liquid state determination test tube 10a shown in Figure 4(a) and the temperature measurement test tube 10b shown in Figure 4(b) up to the 11A line. The two test tubes 10a and 10b are placed upright in a low-temperature constant-temperature water bath at the set temperature so that the 12B line is below the water surface. The thermometer is positioned so that its lower end is 30 mm below the 11A line.

[0021] The sample temperature is maintained at the set temperature ±0.1°C for 10 minutes. After 10 minutes, the liquid state determination test tube 10a is removed from the low-temperature constant-temperature water bath and immediately placed horizontally on a horizontal test stand. The time it takes for the liquid level inside the test tube to move from line 11A to line 12B is measured with a stopwatch and recorded.

[0022] Resins measured for 90 seconds or less are classified as liquid resins. Any sample measuring for more than 90 seconds will be classified as a solid resin. Unless otherwise specified, the determination of whether a substance is liquid or solid will be made at a set temperature of 25°C.

[0023] <Overview of Resin Composition> A resin composition according to one embodiment of the present invention is a resin composition for bonding an optical fiber to a groove in a silicon chip. Specifically, the silicon chip has an optical waveguide for optical connection to an optical fiber. The silicon chip also has a groove formed therein for installing the optical fiber connected to the optical waveguide. The resin composition according to this embodiment is a resin composition that can function as an adhesive for bonding an optical fiber to this groove.

[0024] The resin composition according to this embodiment comprises (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator. Furthermore, the resin composition according to this embodiment may or may not contain (E) inorganic particles. The amount of (E) inorganic particles is below a specific threshold relative to 100% by mass of all components of the resin composition.

[0025] The resin composition according to this embodiment can have high viscosity and can bond optical fibers to the grooves of silicon chips with a small amount of exposure. Furthermore, according to the resin composition according to this embodiment, a cured product with high transparency at communication wavelengths commonly used in silicon photonics, such as 1310 nm, can be obtained.

[0026] The mechanism by which the above-mentioned excellent effects are obtained will be explained below. However, the technical scope of the present invention is not limited to the mechanism described below.

[0027] Generally, in epoxy resin polymerization, the growth reaction is slow, so the carbon chains of the polymers obtained by reacting epoxy resins tend to be short. Therefore, the cured products of compositions containing such epoxy resins tend to be highly brittle, making them prone to delamination due to fracture, and as a result, high adhesive strength may not be obtained.

[0028] On the other hand, oxetane resins can generally produce high molecular weight polymers through cationic polymerization. Therefore, it was expected that using oxetane resins would yield adhesives with high mechanical strength after curing. However, oxetane resins tend to have a slow polymerization initiation, and polymerization is difficult to achieve with low exposure levels.

[0029] Furthermore, thin films of SiOx, SiNx, or SiON may be formed on silicon chips. Silicon chips with these thin films tend to have poorer adhesive wettability compared to glass chips and quartz chips. Therefore, when an adhesive is formed on a silicon chip with a thin film, if fine phase separation occurs in the adhesive, the adhesion of the separated resin portion tends to be particularly poor. Thus, suppressing the occurrence of fine phase separation is desirable for bonding silicon chips.

[0030] Therefore, in this embodiment, an oxetane resin and an epoxy resin are combined. Epoxy resins generally tend to have a fast initiation reaction. Thus, when an oxetane resin and an epoxy resin are combined, the epoxy resin starts the reaction first, generating a large number of initiating species. In such an environment where many initiating species are generated, the oxetane resin starts its reaction, thus reducing the amount of exposure required to advance the curing reaction of the resin composition containing the oxetane resin and epoxy resin as a whole.

[0031] As mentioned above, if only liquid epoxy resin is used as the epoxy resin combined with oxetane resin, the viscosity of the resin composition tends to be low. Also, since liquid epoxy resins generally have short molecular chains, the molecular chains of the polymer obtained after polymerization tend to be short as well. Therefore, a cured product with high mechanical strength cannot be obtained unless the reaction proceeds sufficiently, and the amount of exposure required to allow sufficient curing to obtain high adhesive strength tends to be large.

[0032] On the other hand, if only solid epoxy resin is used as the epoxy resin combined with the oxetane resin as described above, a high-viscosity resin composition can be expected. However, because solid epoxy resin has long molecular chains, the molecules do not move easily within the system. Therefore, the reaction proceeds slowly, and the amount of exposure required to allow sufficient curing to obtain high adhesive strength tends to be large.

[0033] Therefore, in this embodiment, a combination of solid epoxy resin and liquid epoxy resin is used as the epoxy resin. With this combination, the viscosity of the resin composition can be increased by the solid epoxy resin. In addition, since the molecules of the liquid epoxy resin move easily within the system, the solid epoxy resin can suppress the inhibition of the reaction. Thus, while increasing the viscosity of the resin composition, the amount of exposure required to allow sufficient curing to obtain high adhesive strength can be reduced.

[0034] Furthermore, in this embodiment, aliphatic resins such as (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin are used. Because aliphatic resins have a more flexible molecular skeleton compared to aromatic resins, they are more prone to molecular entanglement, and thus the viscosity of the resin composition can be effectively increased.

[0035] Furthermore, since (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin are all aliphatic resins, their compatibility is high. Therefore, the occurrence of fine phase separation in the cured product can be suppressed, and thus the formation of phase interfaces that become the starting point of fracture can be suppressed. Consequently, the mechanical strength of the cured product can be effectively increased, and the degree of curing required to achieve the desired adhesive strength can be reduced. Therefore, it is possible to reduce the amount of exposure. In addition, because the occurrence of fine phase separation can be suppressed due to this high compatibility, the reflection of light at the phase interface can be suppressed, and thus the transparency of the cured product at communication wavelengths can usually be increased.

[0036] Furthermore, generally speaking, once the reaction of oxetane resins begins, the reaction tends to proceed rapidly. When the reaction of oxetane resins proceeds rapidly, the curing of the resin composition proceeds rapidly, and curing stress tends to remain in the cured product. If this stress remains, the cured product is more likely to break, and thus delamination may occur. However, the aliphatic chains contained in (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin used in this embodiment are more flexible than aromatic chains, and therefore can alleviate the aforementioned residual stress. As a result, delamination due to residual stress can be suppressed, and the degree of curing required to achieve the desired adhesive strength can be reduced. Consequently, it is possible to reduce the amount of exposure.

[0037] Furthermore, the resin composition relating to this embodiment contains few (E) inorganic particles or no (E) inorganic particles. In a system containing a combination of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin, (E) inorganic particles have low affinity with resin components other than the (E) inorganic particles. Therefore, if there are many (E) inorganic particles, stress concentrates at the interface between the (E) inorganic particles and the resin components, causing the cured product to fracture starting from that interface and making delamination likely. In contrast, in this embodiment, since there are few (E) inorganic particles or no (E) inorganic particles, fracture of the cured product starting from the interface between the (E) inorganic particles and the resin components can be suppressed. Therefore, the mechanical strength of the cured product required to achieve the desired adhesive strength can be reduced, and thus the degree of curing of the resin composition can be reduced. Consequently, it is possible to reduce the amount of exposure. In addition, by having few (E) inorganic particles or no (E) inorganic particles, the reflection of light from the surface of the (E) inorganic particles can be suppressed, which usually improves the transparency of the cured product at communication wavelengths.

[0038] <(A) Aliphatic liquid oxetane resin> The resin composition according to this embodiment includes (A) an aliphatic liquid oxetane resin as component (A). (A) refers to a liquid aliphatic oxetane resin. Furthermore, an aliphatic oxetane resin refers to a resin containing an oxetane ring and an aliphatic group. In addition, it is preferable that (A) the aliphatic oxetane resin does not contain an aromatic ring. An aromatic ring refers to a ring that follows Hückel's rule, in which the number of electrons in the π-electron system on the ring is 4p+2 (where p is a natural number). The (A) aliphatic liquid oxetane resin can react when (D) the photocationic polymerization initiator is exposed to light and generates cations, thereby curing the resin composition.

[0039] (A) The number of oxetane rings contained in one molecule of an aliphatic liquid oxetane resin is usually one or more, preferably two or more, and may be two.

[0040] (A) The aliphatic groups contained in the aliphatic liquid oxetane resin may be linear, branched, or cyclic, with linear or branched being preferred, and linear being more preferred. The aliphatic groups may be saturated or unsaturated, but saturated aliphatic groups are preferred. For example, (A) the aliphatic liquid oxetane resin may contain monovalent or divalent or more aliphatic groups. The number of carbon atoms in these aliphatic groups is usually 1 or more, preferably 2 or more, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less. Preferred examples of such aliphatic groups include monovalent or divalent or more linear hydrocarbon groups. Specific examples of these linear hydrocarbon groups include alkyl groups such as methyl, ethyl, propyl, and butyl groups; and alkylene groups such as methylene, ethylene, propylene, and butylene groups.

[0041] (A) Examples of aliphatic liquid oxetane resins include the resins listed below (a-1) to (a-5).

[0042] [ka]

[0043] (A) Commercially available aliphatic liquid oxetane resins may be used. (A) Examples of commercially available aliphatic liquid oxetane resins include "OXT-101" (resin of formula (a-1)), "OXT-212" (resin of formula (a-2)), and "OXT-221" (resin of formula (a-3)) from Toagosei's ARON OXETANE series; and "EHO" (resin of formula (a-1)), "HBOX" (resin of formula (a-4)), and "OXMA" (resin of formula (a-5)) from UBE's ETERNACOLL series.

[0044] (A) The aliphatic liquid oxetane resin may be used alone or in combination of two or more types.

[0045] (A) Aliphatic liquid oxetane resin can be liquid at room temperature and therefore can have a low viscosity. For example, the viscosity range of (A) aliphatic liquid oxetane resin at 25°C is preferably 0.1 mPa·s or more, more preferably 1 mPa·s or more, even more preferably 7 mPa·s or more, preferably 100 mPa·s or less, more preferably 25 mPa·s or less, and even more preferably 16 mPa·s or less. Viscosity can be measured using an E-type viscometer (for example, "RE-80U" manufactured by Toki Sangyo Co., Ltd., 1°34' × R24 cone).

[0046] (A) The range of the amount of aliphatic liquid oxetane resin is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 25 parts by mass or more, preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 35 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin. When the amount of (A) aliphatic liquid oxetane resin is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small exposure amount can be achieved at a high level.

[0047] (A) The amount of aliphatic liquid oxetane resin is preferably 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less, based on 100% by mass of the total amount of the resin composition. (A) When the amount of aliphatic liquid oxetane resin is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small amount of exposure can be achieved at a high level.

[0048] The total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin is preferably 80% by mass or more, more preferably 85% by mass or more, and even more preferably 90% by mass or more, and may be 95% by mass or more, based on 100% by mass of the total amount of the resin composition. The upper limit is preferably 99.9% by mass or less, and more preferably 99.5% by mass or less. When the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small amount of exposure can be achieved at a high level.

[0049] (B) Aliphatic solid epoxy resin The resin composition according to this embodiment includes (B) an aliphatic solid epoxy resin as component (B). (B) an aliphatic solid epoxy resin refers to a solid aliphatic epoxy resin. Furthermore, an aliphatic epoxy resin refers to a resin containing epoxy groups and aliphatic groups. (B) an aliphatic solid epoxy resin does not include any of the above-mentioned components (A). Furthermore, it is preferable that (B) an aliphatic solid epoxy resin does not contain aromatic rings. (B) an aliphatic solid epoxy resin can react when (D) a photocationic polymerization initiator is exposed to light and generates cations, thereby curing the resin composition.

[0050] (B) The number of epoxy groups contained in one molecule of the aliphatic solid epoxy resin is usually one or more, preferably two or more. The epoxy groups may be directly or via linking groups bonded to the non-aromatic carbon rings contained in the aliphatic solid epoxy resin. For example, epoxy groups, glycidyl groups, or glycidyloxy groups may be bonded to the non-aromatic carbon rings contained in the aliphatic solid epoxy resin.

[0051] (B) The aliphatic groups contained in the aliphatic solid epoxy resin may be linear, branched, or cyclic, with cyclic being preferred. The aliphatic groups may be saturated or unsaturated, but saturated aliphatic groups are preferred. For example, (B) the aliphatic solid epoxy resin may contain monovalent or divalent or more aliphatic groups. The number of carbon atoms in these aliphatic groups is usually 1 or more, preferably 2 or more, and more preferably 6 or more. The upper limit of the number of carbon atoms is preferably 20 or less, more preferably 15 or less, and may be 10 or less. A preferred example of an aliphatic group is a monovalent or divalent or more cyclic aliphatic hydrocarbon group.

[0052] The aforementioned cyclic aliphatic hydrocarbon groups generally include non-aromatic carbon rings in which carbon atoms constitute the ring atoms. These non-aromatic carbon rings are preferably 4 to 14-membered rings, and more preferably 6-membered rings. Therefore, (B) the aliphatic solid epoxy resin is more preferably an aliphatic epoxy resin containing a 6-membered ring (6-membered ring-containing epoxy resin). Specific examples of non-aromatic carbon rings include monocycloalkane rings such as cyclobutane rings, cyclopentane rings, cyclohexane rings, cycloheptane rings, and cyclooctane rings; and monocycloalkene rings such as cyclobutene rings, cyclopentene rings, cyclohexene rings, cycloheptene rings, cyclooctene rings, cyclopentadiene rings, and cyclohexadiene rings. Among these, monocycloalkane rings are preferred, and cyclohexane rings are more preferred.

[0053] The (B) aliphatic solid epoxy resin containing a cyclic aliphatic hydrocarbon group may be a hydrogenated epoxy resin. "Hydrogenated epoxy resin" refers to an epoxy resin obtained by hydrogenating an aromatic ring-containing epoxy resin such as a bisphenol A type epoxy resin or a bisphenol F type epoxy resin. The hydrogenation rate of the hydrogenated epoxy resin is preferably 50% or more, more preferably 70% or more. The upper limit of the hydrogenation rate is usually 100%, but it may be less than 100%.

[0054] (B) Examples of aliphatic solid epoxy resins include hydrogenated bisphenol A type epoxy resin, aliphatic epoxy resin containing a cyclohexane ring, alicyclic epoxy resin containing a dicyclopentadiene skeleton, polyethylene glycol diglycidyl ether, and epoxy resin having an aliphatic polycyclic skeleton. Here, hydrogenated bisphenol A type epoxy resin refers to an epoxy resin obtained by hydrogenating a bisphenol A type epoxy resin.

[0055] From the viewpoint of significantly obtaining the effects of the present invention, it is preferable that (B) the aliphatic solid epoxy resin comprises one or more selected from the group consisting of hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a 6-membered ring. The distinction between hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a 6-membered ring is not mutually exclusive; for example, the hydrogenated bisphenol A type epoxy resin may be an aliphatic epoxy resin containing a 6-membered ring.

[0056] (B) Commercially available aliphatic solid epoxy resins may be used. (B) Examples of commercially available aliphatic solid epoxy resins include Mitsubishi Chemical's "YX8040" (hydrogenated bisphenol A type epoxy resin); Daicel's "EHPE3150" (alicyclic epoxy resin containing a poly(glycidylcyclohexyleneoxy) structure); DIC's "HP-7200" (alicyclic epoxy resin containing a dicyclopentadiene skeleton); and ENEOS's "DE-102" and "DE-103" (both epoxy resins having an aliphatic polycyclic skeleton).

[0057] (B) Aliphatic solid epoxy resins may be used individually or in combination of two or more types.

[0058] (B) The epoxy equivalent of the aliphatic solid epoxy resin is preferably 50 g / eq. or more, more preferably 60 g / eq. or more, even more preferably 80 g / eq. or more, and particularly preferably 110 g / eq. or more, preferably 5,000 g / eq. or less, more preferably 3,000 g / eq. or less, even more preferably 2,000 g / eq. or less, and particularly preferably 1,000 g / eq. or less. The epoxy equivalent represents the mass of resin per equivalent of epoxy groups. This epoxy equivalent can be measured according to JIS K7236.

[0059] (B) The weight-average molecular weight (Mw) of the aliphatic solid epoxy resin is preferably in the range of 100 to 5,000, more preferably 250 to 3,000, and even more preferably 400 to 1,500. The weight-average molecular weight can be measured as a polystyrene equivalent by gel permeation chromatography (GPC).

[0060] (B) The range of the amount of aliphatic solid epoxy resin is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, even more preferably 55 parts by mass or more, preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 65 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin and (C) aliphatic liquid epoxy resin. When the amount of (B) aliphatic solid epoxy resin is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small exposure amount can be achieved at a high level.

[0061] (B) The aliphatic solid epoxy resin is preferably in greater quantity by mass than (A) the aliphatic liquid oxetane resin. The mass ratio of (A) the aliphatic liquid oxetane resin to (B) the aliphatic solid epoxy resin ((B) aliphatic solid epoxy resin / (A) aliphatic liquid oxetane resin) is preferably 1.1 or more, more preferably 1.2 or more, even more preferably 1.6 or more, preferably 10 or less, more preferably 6 or less, and even more preferably 3 or less. When the mass ratio ((B) aliphatic solid epoxy resin / (A) aliphatic liquid oxetane resin) is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small exposure amount can be achieved at a high level.

[0062] <(C) Aliphatic liquid epoxy resin> The resin composition according to this embodiment includes (C) an aliphatic liquid epoxy resin as component (C). (C) refers to a liquid aliphatic epoxy resin. (C) does not include components (A) to (B) described above. (C) preferably does not contain aromatic rings. (C) can react with (D) a photocationic polymerization initiator when it is exposed to light and generates cations, thereby curing the resin composition.

[0063] (C) The number of epoxy groups contained in one molecule of an aliphatic liquid epoxy resin is usually one or more, preferably two or more. The epoxy groups may be directly bonded to the non-aromatic carbon rings contained in the (C) aliphatic liquid epoxy resin or via linking groups. In addition, the carbon atoms that form the epoxy groups may be included in part of the non-aromatic carbon rings contained in the (C) aliphatic liquid epoxy resin. That is, an epoxy group may be formed by the bonding of an oxygen atom to two carbon atoms that form a non-aromatic carbon ring contained in the (C) aliphatic liquid epoxy resin.

[0064] (C) The aliphatic groups contained in the aliphatic liquid epoxy resin may be selected from the range described for the aliphatic groups contained in the aliphatic solid epoxy resin (B). In this case, the aliphatic groups contained in the aliphatic liquid epoxy resin (C) and the aliphatic groups contained in the aliphatic solid epoxy resin (B) may be the same or different. The preferred range for the aliphatic groups contained in the aliphatic liquid epoxy resin (C) may be the same as the preferred range for the aliphatic groups contained in the aliphatic solid epoxy resin (B).

[0065] (C) When the aliphatic liquid epoxy resin contains a cyclic aliphatic hydrocarbon group, the range of non-aromatic carbon rings that can be included in the cyclic aliphatic hydrocarbon group may be the same as the range of non-aromatic carbon rings that can be included in (B) the aliphatic solid epoxy resin. Among these, monocycloalkane rings are preferred, and cyclohexane rings are more preferred.

[0066] The (C) aliphatic liquid epoxy resin containing cyclic aliphatic hydrocarbon groups may be a hydrogenated epoxy resin. The hydrogenation rate of the hydrogenated epoxy resin is preferably 50% or more, more preferably 70% or more. The upper limit of the hydrogenation rate is usually 100%, but may be less than 100%.

[0067] (C) Examples of aliphatic liquid epoxy resins include hydrogenated bisphenol A type epoxy resins; aliphatic epoxy resins containing a cyclohexane ring; alicyclic epoxy resins containing a dicyclopentadiene skeleton; aliphatic polycyclic epoxy resins; resins obtained by glycidyl etherification of aliphatic diols, aliphatic triols, aliphatic tetraols, aliphatic pentaols, or aliphatic hexaols.

[0068] From the viewpoint of significantly obtaining the effects of the present invention, it is preferable that (C) the aliphatic liquid epoxy resin contains one or more selected from the group consisting of hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a 6-membered ring.

[0069] (C) Commercially available aliphatic liquid epoxy resins may be used. (C) Examples of commercially available aliphatic liquid epoxy resins include Mitsubishi Chemical's "YX8000D" (hydrogenated bisphenol A type epoxy resin, the resin in (c-1) below), "YX7400N", and "YED216N"; Daicel's "Celoxide 2021P" (alicyclic epoxy resin containing a cyclohexane ring, the resin in (c-2) below); ADEKA's "EP-4088L" (alicyclic epoxy resin containing a dicyclopentadiene skeleton); Nagase ChemteX's "EX-321L", "EX-1610", "EX-212L", "EX-214L", "EX810P", "EX991L", and "EX121"; and ENEOS's "THI-DE".

[0070] [ka]

[0071] (C) Aliphatic liquid epoxy resin may be used alone or in combination of two or more types.

[0072] (C) The epoxy equivalent range of aliphatic liquid epoxy resin may be the same as (B) the epoxy equivalent range of aliphatic solid epoxy resin.

[0073] (C) The range of the weight-average molecular weight (Mw) of the aliphatic liquid epoxy resin may be the same as the range of the weight-average molecular weight of the aliphatic solid epoxy resin (B).

[0074] (C) The aliphatic liquid epoxy resin can be liquid at room temperature and therefore can have a low viscosity. (C) The viscosity of the aliphatic liquid epoxy resin may be lower than that of (A) the aliphatic liquid oxetane resin, but it is preferable that it be higher. (C) The viscosity range of the aliphatic liquid epoxy resin at 25°C is preferably 10 mPa·s or more, more preferably 100 mPa·s or more, even more preferably 200 mPa·s or more, preferably 500,000 mPa·s or less, more preferably 100,000 mPa·s or less, and even more preferably 80,000 mPa·s or less.

[0075] (C) The range of the amount of aliphatic liquid epoxy resin is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 5 parts by mass or more, preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin and (C) aliphatic liquid epoxy resin. When the amount of (C) aliphatic liquid epoxy resin is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small exposure amount can be achieved at a high level.

[0076] (C) The amount of aliphatic liquid epoxy resin is preferably less by mass than (A) the aliphatic liquid oxetane resin. The mass ratio of (A) the aliphatic liquid oxetane resin to (C) the aliphatic liquid epoxy resin ((C) aliphatic liquid epoxy resin / (A) aliphatic liquid oxetane resin) is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.10 or more, preferably 0.9 or less, more preferably 0.7 or less, and even more preferably 0.6 or less. When the mass ratio ((C) aliphatic liquid epoxy resin / (A) aliphatic liquid oxetane resin) is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small amount of exposure can be achieved at a high level.

[0077] (D) Photocation polymerization initiator The resin composition according to this embodiment includes a photocationic polymerization initiator as component (D). The photocationic polymerization initiator (D) does not include components (A) to (C) described above. The photocationic polymerization initiator (D) generates cations upon receiving light and can initiate the reaction of components (A) to (C).

[0078] (D) As a photocationic polymerization initiator, for example, a compound that can generate an acid upon irradiation with active light may be used. Examples of such (D) photocationic polymerization initiators include oxime ester compounds, halogen-containing compounds, onium salt compounds, diazoketone compounds, sulfone compounds, sulfonic acid compounds, sulfonimide compounds, diazomethane compounds, etc. Among these, onium salt compounds are preferred.

[0079] (D) Examples of onium salt compounds that can be suitably used as photocationic polymerization initiators include iodonium salts, sulfonium salts, phosphonium salts, diazonium salts, pyridinium salts, etc. Suitable specific examples of onium salt compounds include tris(4-methylphenyl)sulfonium trifluoromethanesulfonate, tris(4-methylphenyl)sulfonium hexafluorophosphonate, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium p-toluenesulfonate, diphenyliodonium hexafluoroantimonate, diphenyliodonium hexafluorophosphate, diphenyliodonium tetrafluoroborate, and diphenyl[4-(phenylthio)phenyl]sulfonium tetrakis(pentafluorophenyl Examples include borate, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate, triphenylsulfonium trifluilomethanesulfonate, triphenylsulfonium p-toluenesulfonate, triphenylsulfonium hexafluoroantimonate, 4-tert-butylphenyl·diphenylsulfonium trifluoromethanesulfonate, 4-tert-butylphenyl·diphenylsulfonium p-toluenesulfonate, and 4,7-di-n-butoxynaphthyltetrahydrothiophenium trifluilomethanesulfonate.

[0080] (D) As a photocationic polymerization initiator, for example, an onium gallate salt having a triarylsulfonium cation and a gallate anion may be used. An example of a triarylsulfonium cation is the compound represented by the following formula (d-1).

[0081] [ka]

[0082] In equation (d-1), R d1 , R d2 , R d3 and R d4each independently represent a group selected from the group consisting of an alkyl group, a hydroxy group, an alkoxy group, an alkylcarbonyl group, an arylcarbonyl group, an alkoxycarbonyl group, an aryloxycarbonyl group, an arylthiocarbonyl group, an acyloxy group, an arylthio group, an alkylthio group, an aryl group, a heterocyclic hydrocarbon group, an aryloxy group, an alkylsulfinyl group, an arylsulfinyl group, an alkylsulfonyl group, an arylsulfonyl group, a hydroxy(poly)alkyleneoxy group, a group that condenses with the benzene ring to which it is bonded to form a condensed polycyclic hydrocarbon skeleton, a substituted or unsubstituted silyl group, a substituted or unsubstituted amino group, a cyano group, a nitro group, and a halogen atom.

[0083] R d1 to R d4 Examples of the alkyl group in the above include linear alkyl groups having 1 to 18 carbon atoms such as methyl group, ethyl group, n-propyl group, n-butyl group, n-pentyl group, n-octyl group, n-decyl group, n-dodecyl group, n-tetradecyl group, n-hexadecyl group and n-octadecyl group; branched alkyl groups having 3 to 18 carbon atoms such as isopropyl group, isobutyl group, sec-butyl group, tert-butyl group, isopentyl group, neopentyl group, tert-pentyl group, isohexyl group and isooctadecyl group; and cycloalkyl groups having 3 to 18 carbon atoms such as cyclopropyl group, cyclobutyl group, cyclopentyl group, cyclohexyl group and 4-decylcyclohexyl group.

[0084] R d1 to R d4 Examples of the alkoxy group in the above include linear alkoxy groups having 1 to 18 carbon atoms and branched alkoxy groups having 3 to 18 carbon atoms. Specific examples thereof include methoxy group, ethoxy group, propoxy group, isopropoxy group, butoxy group, isobutoxy group, sec-butoxy group, tert-butoxy group, hexyloxy group, decyloxy group, dodecyloxy group and octadecyloxy group.

[0085] R d1 to R d4Examples of aryl groups in this context include aryl groups having 6 to 10 carbon atoms, such as phenyl, tolyl, dimethylphenyl, and naphthyl groups.

[0086] R d1 ~R d4 The rings in the condensed polycyclic hydrocarbon skeleton may be two or more rings, or six or fewer rings, preferably four or fewer rings, more preferably three or fewer rings. The condensed polycyclic hydrocarbon skeleton may have a skeleton in which cyclic hydrocarbons with different numbers of rings, such as a five-membered ring and a six-membered ring, are fused together. Examples of such condensed polycyclic hydrocarbon skeletons include the fluorene skeleton and derivatives of the fluorene skeleton. The condensed polycyclic hydrocarbon skeleton may also be a phenanthrene skeleton, and one or two substituents, such as alkyl groups, may be attached to the 9-position of the phenanthrene skeleton.

[0087] R d1 ~R d4 Examples of substituents in the above formula (d-1) include R d1 ~R d4 The same base that was listed as such can be cited.

[0088] In equation (d-1), a d , b d , c d and d d These are, respectively, R d1 , R d2 , R d3 and R d4 It represents the number of a d b represents an integer from 1 to 5. d This represents an integer from 0 to 4. d and d d Each of these independently represents an integer between 0 and 5.

[0089] Examples of gallate anions include compounds represented by the following formula (d-2).

[0090] [ka]

[0091] In equation (d-2), R d13 , R d14 , R d15 and R d16 Each of these independently represents a substituted or unsubstituted phenyl group or perfluoroalkyl group. The substituents substituted for the phenyl group are preferably groups selected from the group consisting of perfluoroalkyl groups, perfluoroalkoxy groups, nitro groups, cyano groups, acyl groups, and halogen atoms.

[0092] R d13 ~R d16 In this, the number of carbon atoms in the perfluoroalkyl group is preferably 1 to 8, more preferably 1 to 4. Specific examples of perfluoroalkyl groups include linear perfluoroalkyl groups such as trifluoromethyl, pentafluoroethyl, heptafluoropropyl, nonafluorobutyl, perfluoropentyl, and perfluorooctyl groups; branched perfluoroalkyl groups such as heptafluoroisopropyl, nonafluoroisobutyl, nonafluoro-sec-butyl, and nonafluoro-tert-butyl groups; and perfluorocycloalkyl groups such as perfluorocyclopropyl, perfluorocyclobutyl, perfluorocyclopentyl, and perfluorocyclohexyl groups.

[0093] R d13 ~R d16 In this, the number of carbon atoms in the perfluoroalkoxy group is preferably 1 to 8, more preferably 1 to 4. Specific examples of perfluoroalkoxy groups include linear perfluoroalkoxy groups such as trifluoromethoxy, pentafluoroethoxy, heptafluoropropoxy, nonafluorobutoxy, perfluoropentyloxy, and perfluorooctyloxy; and branched perfluoroalkoxy groups such as heptafluoroisopropoxy, nonafluoroisobutoxy, nonafluoro-sec-butoxy, and nonafluoro-tert-butoxy.

[0094] R d13 ~R d16Examples of halogen atoms include fluorine, chlorine, bromine, and iodine atoms.

[0095] From the perspective of cationic polymerization performance, R d13 ~R d16 A phenyl group substituted with at least one selected from the group consisting of perfluoroalkyl groups and fluorine atoms is preferred. d13 , R d14 , R d15 and R d16 They may be the same or they may be different.

[0096] An example of the gallate anion mentioned above is (C6F5)4Ga - , ((CF3)2C6H3)4Ga - (CF3C6H4)4Ga - , (C6F5)2GaF2 - , C6F5GaF3 - (C6H3F2)4Ga - These are some examples.

[0097] (D) Commercially available photocationic polymerization initiators may be used. Examples of commercially available (D) photocationic polymerization initiators include onium salt compounds such as "TS-01" and "TS-91" from Sanwa Chemical Co., Ltd.; "CPI-110A", "CPI-110B", "CPI-110P", "CPI-210S", "HS-1", "LW-S1", "IK-1", "CPI-310B", and [CPI-310FG] from Sunapro Co., Ltd.; and "SI-110L", "SI-180L", and "SI-100L" from Sanshin Chemical Industry Co., Ltd.

[0098] (D) The photocationic polymerization initiator may be used alone or in combination of two or more types.

[0099] (D) The range of the amount of photocationic polymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin and (C) aliphatic liquid epoxy resin. (D) When the amount of photocationic polymerization initiator is within the above range, both high viscosity of the resin composition and adhesion of the optical fiber to the groove of the silicon tip with a small amount of exposure can be achieved at a high level.

[0100] <(E) Inorganic particles> The resin composition according to this embodiment may or may not contain inorganic particles (E) as component (E). The amount of inorganic particles (E) in the resin composition is usually 15% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 0.1% by mass or less, based on 100% by mass of the total amount of the resin composition. Since the resin composition does not have to contain inorganic particles (E), the lower limit is usually 0% by mass or more, and may be 0% by mass.

[0101] (E) Inorganic compounds are used as the material for the inorganic particles. (E) Examples of materials for the inorganic particles include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica and alumina are preferred, and silica is even more preferred. Therefore, (E) inorganic particles preferably contain silica, and may contain only silica. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Spherical silica is preferred as the silica. (E) Inorganic particles may be used individually or in combination of two or more types.

[0102] (E) Examples of commercially available inorganic particles include "SP60-05" and "SP507-05" from Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" from Admatex Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" from Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" from Tokuyama Corporation; "Cellspheres" and "MGH-005" from Taiheiyo Cement Corporation; "Esferique" and "BA-1" from JGC Catalysts & Chemicals Co., Ltd.; and "200" from Nippon Aerosil Co., Ltd.

[0103] (E) The average particle size of the inorganic particles is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, and even more preferably 1 μm or less.

[0104] (E) The average particle size of inorganic particles can be measured by the laser diffraction-scattering method based on Mie scattering theory. Specifically, the particle size distribution of inorganic particles can be created on a volume basis using a laser diffraction-scattering particle size distribution analyzer, and the average particle size can be measured by taking the median diameter as the average particle size. A sample can be prepared by weighing 100 mg of inorganic particles and 10 g of methyl ethyl ketone into a vial and dispersing them with ultrasound for 10 minutes. The sample can be measured using a laser diffraction-type particle size distribution analyzer with blue and red light source wavelengths, using a flow cell method to measure the volume-based particle size distribution of inorganic particles, and the average particle size can be calculated as the median diameter from the obtained particle size distribution. An example of a laser diffraction-type particle size distribution analyzer is the "LA-960" manufactured by Horiba, Ltd.

[0105] (E) The specific surface area of ​​the inorganic particles is preferably 0.1 m². 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 It is 100m or more / g, preferably 100m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 It is less than / g. (E) The specific surface area of ​​inorganic particles can be measured by adsorbing nitrogen gas onto the sample surface using a specific surface area measuring device (Macsorb HM-1210, manufactured by Mountec) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0106] (E) Inorganic particles are preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of surface treatment agents include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. One type of surface treatment agent may be used alone, or two or more types may be used in combination.

[0107] Examples of commercially available surface treatment agents include "KBM403" (3-glycidoxypropyltrimethoxysilane), "KBM803" (3-mercaptopropyltrimethoxysilane), "KBE903" (3-aminopropyltriethoxysilane), "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), "SZ-31" (hexamethyldisilazane), "KBM103" (phenyltrimethoxysilane), "KBM-4803" (long-chain epoxy-type silane coupling agent), and "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane), all manufactured by Shin-Etsu Chemical Co., Ltd.

[0108] From the viewpoint of improving the dispersibility of inorganic particles, the degree of surface treatment by the surface treatment agent is preferably within a specific range. Specifically, 100% by mass of inorganic particles is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably with 0.2% to 3% by mass of the surface treatment agent, and even more preferably with 0.3% to 2% by mass of the surface treatment agent.

[0109] The degree of surface treatment by a surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic particles. From the viewpoint of improving the dispersibility of inorganic particles, the amount of carbon per unit surface area of ​​the inorganic particles should be 0.02 mg / m². 2 The above is preferred, and 0.1 mg / m² 2 The above is more preferable, 0.2 mg / m²2 The above is even more preferable. On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition, 1.0 mg / m² 2 The following is preferred: 0.8 mg / m² 2 The following is more preferable: 0.5 mg / m² 2 The following are even more preferable.

[0110] (E) The amount of carbon per unit surface area of ​​inorganic particles can be measured after washing the surface-treated inorganic particles with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as the solvent is added to the inorganic particles that have been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solids, the amount of carbon per unit surface area of ​​the inorganic particles can be measured using a carbon analyzer. As a carbon analyzer, a Horiba "EMIA-320V" or similar can be used.

[0111] <(F) Sensitizer> The resin composition according to this embodiment may contain (F) a sensitizer as an optional component. The (F) sensitizer as component (F) does not include those corresponding to components (A) to (E) described above. The (F) sensitizer can generally be excited by light, but the (F) sensitizer itself does not generate cationic species. In addition, when the (F) sensitizer is excited, it can usually transfer its energy to the (D) photocationic polymerization initiator to promote the generation of cationic species. Therefore, the curing of the resin composition can be accelerated by using the (F) sensitizer.

[0112] (F) Examples of sensitizers include benzophenones such as Michla's ketone, 4,4'-bis(diethylamino)benzophenone, and 4-morpholinobenzophenone; cyclic alkanes such as 2,5-bis(4'-diethylaminobenzal)cyclopentane, 2,6-bis(4'-diethylaminobenzal)cyclohexanone, and 2,6-bis(4'-diethylaminobenzal)-4-methylcyclohexanone; chalcones such as 4,4'-bis(dimethylamino)chalcone and 4,4'-bis(diethylamino)chalcone; and p-dimethylaminocinnamyridene. Indanone compounds such as Danone and p-dimethylaminobenzylideneindanone; anthracenes such as 9,10-dibutoxyanthracene (DBA), 9,10-diethoxyanthracene (DEA), 9,10-dipropoxyanthracene, and 9,10-bis(2-ethylhexyloxy)anthracene; thiazole compounds such as 2-(p-dimethylaminophenylbiphenylene)-benzothiazole, 2-(p-dimethylaminophenylvinylene)benzothiazole, and 2-(p-dimethylaminophenylvinylene)isonaphthothiazole; 1,3-bis(4'-dimethyl Acetones such as 1,3-(4'-diethylaminobenzal)acetone; coumarins such as 3,3'-carbonyl-bis(7-diethylaminocoumarin), 3-acetyl-7-dimethylaminocoumarin, 3-ethoxycarbonyl-7-dimethylaminocoumarin, 3-benzyloxycarbonyl-7-dimethylaminocoumarin, 3-methoxycarbonyl-7-diethylaminocoumarin, 3-ethoxycarbonyl-7-diethylaminocoumarin; N-phenyl-N'-ethylethanolamine, N-phenyldiethanolamine Amines such as amine, Np-tolyldiethanolamine, N-phenylethanolamine, isoamyl dimethylaminobenzoate, and isoamyl diethylaminobenzoate; heterocyclic compounds such as 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-(p-dimethylaminostyryl)benzoxazole, 2-(p-dimethylaminostyryl)benzthiazole, 2-(p-dimethylaminostyryl)naphtho(1,2-d)thiazole, 1-phenyl-5-mercaptotetrazol, and 1-p-hydroxyphenyl-5-mercaptotetrazol;Examples include styrenes such as 2-(p-dimethylaminobenzoyl)styrene; among these, anthracenes are preferred.

[0113] (F) The sensitizer may be used alone or in combination of two or more types.

[0114] (F) The range of the amount of sensitizer is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, even more preferably 0.3 parts by mass or more, preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin and (C) aliphatic liquid epoxy resin.

[0115] <(G) Any additives> The resin composition according to this embodiment may further contain (G) any additives as optional components, to the extent that they do not significantly impair the desired effects of the present invention. (G) Any additives as components (G) do not include those corresponding to components (A) to (F) described above. Examples of optional additives (G) include adhesion aids; surfactants such as fluorine-based surfactants, nonionic surfactants, cationic surfactants, anionic surfactants, and silicone-based surfactants; polymerization inhibitors; defoaming agents; flame retardants; thermal cationic polymerization initiators; curable resins other than components (A) to (C) described above; thermoplastic resins; and so on. (G) Any additives may be used individually or in combination of two or more types.

[0116] <(H) Solvent> The resin composition according to this embodiment may further contain a solvent (H) as an optional volatile component in order to dissolve or disperse the solid components such as components (A) to (G) described above. Typically, an organic solvent is used as the solvent (H). Examples of organic solvents include ketone solvents, ester solvents, ether solvents, alcohol solvents, amide solvents, sulfoxide solvents, nitrile solvents, aliphatic hydrocarbon solvents, aromatic hydrocarbon solvents, etc. The solvent (H) may be used alone or in combination of two or more types.

[0117] From the viewpoint of suppressing void formation, it is preferable to have a small amount of (H) solvent. Specifically, the amount of (H) solvent in the resin composition is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0.1% by mass or less, based on 100% by mass of the total amount. Since it is preferable for the resin composition to not contain (H) solvent, the lower limit of the amount of (H) solvent is 0% by mass or more, and 0% by mass is particularly preferable.

[0118] <Properties of resin compositions and their cured products> The resin composition according to this embodiment can be liquid at room temperature. Furthermore, this resin composition can be cured by exposure to light such as ultraviolet light, as the resin components (A) to (C) react and bond together. The cured resin composition obtained by this curing can exhibit sufficiently high adhesive strength to bond optical fibers to the grooves of a silicon chip. Therefore, the resin composition according to this embodiment can function as an adhesive for bonding optical fibers to the grooves of a silicon chip.

[0119] The resin composition according to this embodiment can have high viscosity. For example, the viscosity of the resin composition at 25°C is usually 4 Pa·s or more, preferably 10 Pa·s or more, and more preferably 20 Pa·s or more. The upper limit of viscosity is preferably 200 Pa·s or less, more preferably 160 Pa·s or less, and even more preferably 130 Pa·s or less. Viscosity can be measured using an E-type viscometer (RE-80U, manufactured by Toki Sangyo Co., Ltd., 1°34' × R24 cone).

[0120] As described above, the resin composition according to this embodiment has high viscosity, which can suppress excessive fluidity in the grooves of the silicon chip. Therefore, when the resin composition is used as an adhesive to bond an optical fiber to the grooves of the silicon chip, it is preferable to suppress the outflow of the resin composition to unintended locations. For example, when performing the <Test 4. Appearance Evaluation Test> of the example described later, it is preferable to bond the optical fiber to the V-groove while preventing the resin composition or its cured product from overflowing from the V-groove chip cover.

[0121] According to the resin composition of this embodiment, it is possible to bond an optical fiber to the groove of a silicon chip with a small amount of exposure. Specifically, when bonding an optical fiber to a groove using the resin composition and curing the resin composition by exposure, sufficient adhesive strength to fix the optical fiber to the groove can be obtained with a small amount of exposure. For example, perform <Test 3. Adhesion test between groove and optical fiber> in the example described later. In this case, the minimum exposure required to obtain an adhesive strength sufficient to prevent the optical fiber from peeling off the V groove of the silicon chip is preferably 2000 mJ / cm². 2 More specifically, 500 mJ / cm² 2 More preferably, 100 mJ / cm² 2 The following can be done.

[0122] According to the resin composition of this embodiment, optical fibers can usually be bonded to a silicon member with high adhesive strength, making it possible to bond optical fibers to the grooves of a silicon chip with high adhesive strength. For example, the cured resin composition is bonded to a silicon chip (such as a condenser chip) by performing <Test 1. Adhesion Strength Measurement Test> in the example described later. In this case, the exposure dose is 2000 mJ / cm². 2 The adhesive strength required to peel the chip from the resulting cured product is preferably 12 N / mm². 2 The above is preferably 14 N / mm 2 More preferably 20 N / mm 2 It can be increased to the above. The upper limit of adhesive strength is, for example, 100 N / mm².2 Below, 90N / mm 2 The following, or 80 N / mm 2 The following are possible:

[0123] As described above, the cured product of the resin composition according to this embodiment is cured by the reaction of resins such as components (A) to (C) to form bonds, and therefore may contain components in the resin composition or their reaction products. This cured product can typically have a low absorbance at the communication wavelength used in silicon photonics. For example, the absorbance of the cured product at a wavelength of 1310 nm with an optical path length of 2 mm is measured by performing <Test 5. Measurement test of absorbance of cured resin composition> in the example described later. In this case, the absorbance can be preferably 0.10 or less, more preferably 0.09 or less, even more preferably 0.08 or less, and particularly preferably 0.06 or less.

[0124] <Devices using resin compositions as adhesives> The resin composition according to this embodiment can be used as an adhesive in a bonding method for bonding optical fibers to grooves in a silicon chip. Therefore, by using the resin composition as an adhesive, a device comprising a silicon chip and optical fibers bonded to the grooves of the silicon chip can be obtained. Hereinafter, this device may be referred to as an "optical device".

[0125] Figure 1 is a schematic perspective view showing an optical device 1 according to one embodiment of the present invention. Figure 2 is a schematic cross-sectional view showing an optical device 1 according to one embodiment of the present invention. In Figure 2, a schematic cross-section of the optical device 1 is shown, obtained by cutting the optical device 1 with a plane perpendicular to the direction in which the groove 110 of the silicon chip 100 extends.

[0126] As shown in Figures 1 and 2, the optical device 1 according to this embodiment comprises a silicon chip 100, an optical fiber 200, and an adhesive portion 300 for bonding the silicon chip 100 and the optical fiber 200. The optical device 1 may also optionally include a cover material 400 to cover the optical fiber 200 and the adhesive portion 300.

[0127] Figure 3 is a schematic perspective view showing a silicon chip 100 provided in an optical device 1 according to one embodiment of the present invention. The silicon chip 100 includes an optical waveguide 120 that is optically connectable to an optical fiber 200. Here, an optical waveguide 120 comprising a silicon core 121 and a cladding 122 made of SiO2 covering the core 121 is used as an example, but the optical waveguide 120 is not limited to this. The silicon chip 100 has grooves 110 formed therein for mounting the optical fiber 200 to be connected to the optical waveguide 120.

[0128] The groove 110 is usually formed extending in one direction. Here, as shown in Figure 2, a V-groove with a roughly V-shaped cross-section on the side surface 110S is used as an example for the explanation of the groove 110, but the groove 110 is not limited to a V-groove. For example, the groove 110 may be a groove (e.g., a U-groove) with a rounded cross-section at the bottom 110B, or a groove with a flat bottom surface. Typically, as shown in Figure 3, the groove 110 is formed so that an optical connection can be achieved between the optical fiber 200 and the core 121 of the optical waveguide 120 at the end 110E of the groove 110 on the optical waveguide 120 side.

[0129] The specific cross-sectional shape and dimensions of the groove 110 are preferably set so that the optical fiber 200 can be aligned in the groove 110. Here, the resin composition according to this embodiment has high viscosity and therefore has the advantage of enabling uniform application. From the viewpoint of utilizing this advantage, the resin composition according to this embodiment is suitable for applications in which optical fibers 200 are connected to minute grooves 110 where high precision uniformity is required. Therefore, from the viewpoint of utilizing the advantages of the resin composition according to this embodiment, as shown in Figure 2, the width W of the groove 110 is preferably small, and its specific range is preferably 0.30 mm or less, more preferably 0.20 mm or less, preferably 0.01 mm or more, and more preferably 0.10 mm or more. Also, the depth D of the groove 110 is preferably small, and its specific range is preferably 0.30 mm or less, more preferably 0.20 mm or less, more preferably 0.15 mm or less, preferably 0.01 mm or more, and more preferably 0.10 mm or more. Furthermore, it is preferable that the angle θ that the side surface 110S of the groove 110 makes with respect to the main surface 100U of the chip is small, and its specific range is preferably 70° or less, more preferably 60° or less, even more preferably 55° or less, preferably 20° or more, more preferably 30° or more, and even more preferably 40° or more.

[0130] As shown in Figure 2, the optical fiber 200 is arranged in alignment with the groove 110. The adhesive portion 300 fills the area around the optical fiber 200, bonding it to the groove 110. The adhesive portion 300 includes a cured resin composition, and usually contains only the cured resin. Since the cured resin exhibits excellent adhesive strength, the adhesive portion 300 can stably hold the optical fiber 200 in the groove 110. At this time, the tip of the optical fiber 200 (not shown) may be positioned in contact with the end 110E of the groove 110, or it may be positioned away from the end 110E of the groove 110. When the tip of the optical fiber 200 and the end 110E of the groove 110 are separated, the gap between the tip of the optical fiber 200 and the end 110E of the groove 110 may be filled by the adhesive portion 300. However, since the adhesive portion 300 formed from the cured resin composition according to this embodiment has low absorbance at the communication wavelength, attenuation of the optical signal is suppressed.

[0131] Typically, the cover material 400 is installed so as to cover the optical fiber 200 and the adhesive portion 300 on the groove 110. When the cover material 400 is provided, the adhesive portion 300 is formed in the gap between the silicon chip 100 and the cover material 400, and a configuration is obtained in which the optical fiber 200 is fixed within the adhesive portion 300. Therefore, the cover material 400 can protect the optical fiber 200 and the adhesive portion 300. Furthermore, since the resin composition according to this embodiment does not have excessive fluidity on the silicon chip 100, it is preferable that the formation of the adhesive portion 300 in an unintended location can be suppressed. Specifically, it is possible to suppress the formation of the adhesive portion 300 in a position that protrudes from the cover material 400 when viewed from the thickness direction.

[0132] Such optical device 1 is, for example, Step (I) involves installing the optical fiber 200 in the groove 110 of the silicon chip 100, Step (II) involves applying a resin composition to the groove 110, (IV) A step of curing the resin composition to form the adhesive portion 300, It can be manufactured by a manufacturing method that includes the following. Furthermore, when manufacturing an optical device 1 comprising a lid material 400, the manufacturing method is: Step (III): Placing the lid material 400 on the resin composition applied to the groove 110. It may include.

[0133] In the manufacturing method of the optical device 1, the steps of (I) installing the optical fiber 200 in the groove 110 of the silicon chip 100 and (II) applying the resin composition to the groove 110 may be performed in either order. Therefore, step (I) may be performed after step (II), but it is preferable to perform step (II) after step (I). The resin composition can be applied using an appropriate application device such as a dispenser.

[0134] If a cover material 400 is provided, the manufacturing method of the optical device 1 includes step (III) of placing the cover material 400 on the resin composition after steps (I) and (II) described above. It is preferable to place the cover material 400 so as to cover the entire resin composition applied to the groove 110. The resin composition may spread to fill the space between the silicon chip 100 in which the groove 110 is formed and the cover material 400, but it does not have excessive flow, so preferably, outflow from the cover material 400 when viewed from the thickness direction is suppressed.

[0135] Subsequently, a curing step (IV) of the resin composition is performed. In this step (IV), an exposure treatment is performed in which the resin composition is irradiated with an active light capable of curing the resin composition. The active light is not limited to any light that can cure the resin composition, but ultraviolet light is usually used. The irradiation with the active light may be performed through the silicon chip 100 or through the lid material 400.

[0136] Since the resin composition hardens with a low exposure dose, achieving adhesion between the silicon chip 100 and the optical fiber 200, the exposure dose can be reduced in step (IV). For example, when exposure treatment is performed with ultraviolet light, the exposure dose range is preferably 3000 mJ / cm². 2 More preferably, 2500 mJ / cm² 2 More preferably, 2000 mJ / cm² 2 The following applies. The lower limit is not restricted as long as the desired adhesive strength is obtained, for example, 100 mJ / cm².2 The above is possible. In this way, the resin composition can be cured with a small amount of exposure, and an adhesive portion 300 with sufficient adhesive strength can be formed, thus shortening the manufacturing time of the optical device 1.

[0137] By forming the adhesive portion 300 in step (IV), the optical fiber 200 is bonded to the groove 110 of the silicon chip 100, thereby obtaining the optical device 1. The method for manufacturing this optical device 1 may include any additional steps in combination with steps (I) to (IV).

[0138] For example, the method for manufacturing the optical device 1 may include an annealing step after step (IV) in which the optical device 1 is heated. In the annealing step, for example, the optical device 1 is heated to 120°C or higher. However, from the viewpoint of taking advantage of the benefit of shortening the manufacturing time of the optical device 1, it is preferable that the method for manufacturing the optical device 1 does not include the annealing step. [Examples]

[0139] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to these examples. In the following description, "parts" and "%" refer to "parts by mass" and "mass%" respectively, unless otherwise specified. Unless otherwise specified, the temperature and pressure conditions were room temperature (23°C) and atmospheric pressure (1 atm).

[0140] <Reagent Description> The reagents used in the following examples and comparative examples are as follows. Viscosity values ​​are all expressed at 25°C.

[0141] (A) Aliphatic oxetane compounds: • "OXT-221": "OXT-221" manufactured by Toagosei Co., Ltd., viscosity 9 mPa·s to 14 mPa·s

[0142] (B) Aliphatic solid epoxy resin: • "YX8040": Hydrogenated bisphenol A epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 1000 g / eq. • "EHPE3150": A cyclohexane ring-containing alicyclic epoxy resin, manufactured by Daicel Corporation, epoxy equivalent weight 177 g / eq. • "HP-7200": A cyclopentadiene-containing alicyclic epoxy resin, manufactured by DIC Corporation, with an epoxy equivalent of 254-264 g / eq.

[0143] (C) Aliphatic liquid epoxy resin: • "YX8000D": Hydrogenated bisphenol A epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent weight 185 g / eq., viscosity 0.8 Pa·s • "2021P": A cyclohexane ring-containing alicyclic epoxy resin, manufactured by Daicel Corporation, "Celoxide 2021P", epoxy equivalent 130 g / eq., viscosity 240 mPa·s • "EP-4088L": A cyclopentadiene skeleton-containing alicyclic epoxy resin, manufactured by ADEKA Corporation, epoxy equivalent 165 g / eq., 230 mPa·s

[0144] (D) Photocationic polymerization initiator • "CPI-110P": "CPI-110P" manufactured by Sunapro, diphenyl[4-(phenylthio)phenyl]sulfonium hexafluorophosphate • "CPI-110B": "CPI-110B" manufactured by Sunapro, diphenyl[4-(phenylthio)phenyl]sulfonium-tetra(pentafluorophenyl)borate • "CPI-310FG": "CPI-310FG" manufactured by Sunapro, sulfonium salt

[0145] (E) Inorganic particles: • "Silica Particle 1": Spherical silica (SO-C2, manufactured by Admatex Co., Ltd., with average particle size 0.5 μm and specific surface area 5.8 m²) surface-treated with a silane coupling agent (KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) 2 / g)) • "Silica Particles 2": Fumed silica (manufactured by Nippon Aerosil Co., Ltd., "200", specific surface area 200 m²) 2 / g

[0146] (F) Photosensitizer: • "UVS-1101": Anthracure UVS-1101, manufactured by Air Water Performance Chemicals, 9,10-diethoxyanthracene

[0147] <Example 1> In a plastic container specifically designed for a rotation / revolution mixer ("Awatori Rentaro ARE-310" manufactured by Thinky Co., Ltd.), 30 parts of an aliphatic oxetane compound ("OXT-221" manufactured by Toagosei Co., Ltd.), 60 parts of an aliphatic solid epoxy resin ("YX8040" manufactured by Mitsubishi Chemical Corporation), and 10 parts of an aliphatic liquid epoxy resin ("YX8000D" manufactured by Mitsubishi Chemical Corporation) were weighed out to obtain an intermediate mixture. This intermediate mixture was mixed using the aforementioned rotation / revolution mixer at 2000 rpm until the aliphatic solid epoxy resin was completely dissolved. Then, 1 part of a photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Co., Ltd.) and 0.5 parts of a photosensitizer ("Anthracure UVS-1101" manufactured by Air Water Performance Chemical Co., Ltd.) were added to this intermediate mixture, and the mixture was stirred again with the aforementioned rotation / revolution mixer to obtain resin composition 1.

[0148] <Example 2> Resin composition 2 was prepared by the same method as in Example 1, except that 10 parts of aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") were replaced with 10 parts of aliphatic liquid epoxy resin (Daicel Corporation's "Celoxide 2021P").

[0149] <Example 3> Resin composition 3 was prepared by the same method as in Example 1, except that 60 parts of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) were replaced with 60 parts of aliphatic solid epoxy resin (EHPE3150, manufactured by Daicel Corporation).

[0150] <Example 4> Resin composition 4 was prepared by the same method as in Example 1, except that 60 parts of aliphatic solid epoxy resin (Mitsubishi Chemical Corporation's "YX8040") were replaced with 60 parts of aliphatic solid epoxy resin (Daicel Corporation's "EHPE3150"), and 10 parts of aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") were replaced with 10 parts of aliphatic liquid epoxy resin (Daicel Corporation's "Celoxide 2021P").

[0151] <Example 5> The amount of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) was changed to 30 parts. In addition, 30 parts of aliphatic solid epoxy resin (EHPE3150, manufactured by Daicel Corporation) were added to the intermediate mixture. Furthermore, the amount of aliphatic liquid epoxy resin (YX8000D, manufactured by Mitsubishi Chemical Corporation) was changed to 5 parts. In addition, 5 parts of aliphatic liquid epoxy resin (Celoxide 2021P, manufactured by Daicel Corporation) were added to the intermediate mixture. Except for the above, resin composition 5 was produced by the same method as in Example 1.

[0152] <Example 6> Resin composition 6 was prepared by the same method as in Example 1, except that 60 parts of aliphatic solid epoxy resin (Mitsubishi Chemical Corporation's "YX8040") were replaced with 60 parts of aliphatic solid epoxy resin (DIC Corporation's "HP-7200"), and 10 parts of aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") were replaced with 10 parts of aliphatic liquid epoxy resin (ADEKA Corporation's "EP-4088L").

[0153] <Example 7> The amount of aliphatic oxetane compound (OXT-221, manufactured by Toagosei Co., Ltd.) was changed to 25 parts. The amount of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) was changed to 65 parts. The amount of aliphatic liquid epoxy resin (YX8000D, manufactured by Mitsubishi Chemical Corporation) was changed to 5 parts. Furthermore, 5 parts of aliphatic liquid epoxy resin (Celoxide 2021P, manufactured by Daicel Corporation) were added to the intermediate mixture. Except for the above changes, resin composition 7 was produced by the same method as in Example 1.

[0154] <Example 8> The amount of aliphatic oxetane compound (OXT-221, manufactured by Toagosei Co., Ltd.) was changed to 35 parts. The amount of aliphatic liquid epoxy resin (YX8000D, manufactured by Mitsubishi Chemical Corporation) was changed to 2.5 parts. Furthermore, 2.5 parts of aliphatic liquid epoxy resin (Celoxide 2021P, manufactured by Daicel Corporation) were added to the intermediate mixture. Except for the above changes, resin composition 8 was prepared by the same method as in Example 1.

[0155] <Example 9> The amount of aliphatic solid epoxy resin (Mitsubishi Chemical Corporation's "YX8040") was changed to 55 parts. The amount of aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") was also changed to 7.5 parts. Furthermore, 7.5 parts of aliphatic liquid epoxy resin (Daicel Corporation's "Celoxide 2021P") were added to the intermediate mixture. Except for the above, resin composition 9 was produced by the same method as in Example 1.

[0156] <Example 10> The amount of aliphatic oxetane compound (OXT-221, manufactured by Toagosei Co., Ltd.) was changed to 15 parts. The amount of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) was changed to 75 parts. The amount of aliphatic liquid epoxy resin (YX8000D, manufactured by Mitsubishi Chemical Corporation) was changed to 5 parts. Furthermore, 5 parts of aliphatic liquid epoxy resin (Celoxide 2021P, manufactured by Daicel Corporation) were added to the intermediate mixture. Except for the above, resin composition 10 was prepared by the same method as in Example 1.

[0157] <Example 11> The amount of aliphatic oxetane compound (OXT-221, manufactured by Toagosei Co., Ltd.) was changed to 45 parts. The amount of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) was changed to 52 parts. The amount of aliphatic liquid epoxy resin (YX8000D, manufactured by Mitsubishi Chemical Corporation) was changed to 1.5 parts. Furthermore, 1.5 parts of aliphatic liquid epoxy resin (Celoxide 2021P, manufactured by Daicel Corporation) was added to the intermediate mixture. Except for the above, resin composition 11 was produced by the same method as in Example 1.

[0158] <Example 12> Resin composition 12 was prepared by the same method as in Example 1, except that the amount of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) was changed to 45 parts, and the amount of aliphatic liquid epoxy resin (YX8000D, manufactured by Mitsubishi Chemical Corporation) was changed to 25 parts.

[0159] <Example 13> Resin composition 13 was prepared in the same manner as in Example 1, except that 10 parts of silica particles 1 were added to the intermediate mixture before mixing the photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro) and the photosensitizer ("Anthracure UVS-1101" manufactured by Air Water Performance Chemicals).

[0160] <Example 14> Resin composition 14 was prepared by the same method as in Example 1, except that the amount of photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Co., Ltd.) was changed to 2.5 parts, and the amount of photosensitizer ("Anthracure UVS-1101" manufactured by Air Water Performance Chemical Co., Ltd.) was changed to 2.5 parts.

[0161] <Example 15> Resin composition 15 was prepared by the same method as in Example 1, except that the amount of photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Co., Ltd.) was changed to 0.5 parts.

[0162] <Example 16> Resin composition 16 was prepared in the same manner as in Example 1, except that the amount of photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Corporation) was changed to 0.2 parts, and the amount of photosensitizer ("Anthracure UVS-1101" manufactured by Air Water Performance Chemicals Corporation) was changed to 0.2 parts.

[0163] <Example 17> Resin composition 17 was prepared in the same manner as in Example 1, except that the amount of photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Corporation) was changed to 4 parts, and the amount of photosensitizer ("Anthracure UVS-1101" manufactured by Air Water Performance Chemicals Corporation) was changed to 4 parts.

[0164] <Example 18> Resin composition 18 was prepared in the same manner as in Example 1, except that the amount of photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Co., Ltd.) was changed to 0.5 parts, and 0.5 parts of photocationic polymerization initiator ("CPI-110B" manufactured by Sunapro Co., Ltd.) was added to the intermediate mixture.

[0165] <Example 19> Resin composition 19 was prepared in the same manner as in Example 1, except that 10 parts of silica particles 2 were added to the intermediate mixture before mixing the photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro) and the photosensitizer ("Anthracure UVS-1101" manufactured by Air Water Performance Chemicals).

[0166] <Example 20> Resin composition 20 was prepared by the same method as in Example 1, except that one part of the photocationic polymerization initiator ("CPI-110P" manufactured by Sunapro Co., Ltd.) was replaced with one part of the photocationic polymerization initiator ("CPI-310FG" manufactured by Sunapro Co., Ltd.).

[0167] <Comparative Example 1> Resin composition 18 was prepared by the same method as in Example 1, except that an aliphatic oxetane compound (OXT-221, manufactured by Toagosei Co., Ltd.) was not used, and the amount of aliphatic solid epoxy resin (YX8040, manufactured by Mitsubishi Chemical Corporation) was changed to 90 parts.

[0168] <Comparative Example 2> Resin composition 19 was prepared by the same method as in Example 1, except that aliphatic solid epoxy resin (Mitsubishi Chemical Corporation's "YX8040") was not used, and the amount of aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") was changed to 70 parts.

[0169] <Comparative Example 3> Resin composition 20 was prepared in the same manner as in Example 1, except that the amount of aliphatic solid epoxy resin (Mitsubishi Chemical Corporation's "YX8040") was changed to 70 parts, and aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") was not used.

[0170] <Comparative Example 4> Ten parts of aliphatic liquid epoxy resin (Mitsubishi Chemical Corporation's "YX8000D") were replaced with ten parts of aliphatic liquid epoxy resin (ADEKA Corporation's "EP-4088L"). In addition, 20 parts of silica particles 1 were added to the intermediate mixture before mixing the photocationic polymerization initiator (Sunapro Corporation's "CPI-110P") and the photosensitizer (Air Water Performance Chemicals Corporation's "Anthracure UVS-1101"). Except for the above, resin composition 21 was prepared by the same method as in Example 1.

[0171] <Test 1. Adhesion Strength Measurement Test> A 76mm x 26mm x 1.0mm thick glass slide was prepared. 1mg to 3mg of the resin composition was applied to this glass slide, and a silicon condenser chip (JIS designation 2012 size) was placed on top. The resin composition was cured by photocuring under the following curing conditions 1 to 3. Using a die shear measuring device (Daisi Series 4000), the die shear strength, as an indicator of adhesive strength, was measured by scratching the condenser chip on the cured resin composition at a speed of 200μm / s in an environment of 25°C. The die shear strength represents the magnitude of the force required to peel the condenser chip off by applying force in the in-plane direction (perpendicular to the thickness direction) relative to the condenser chip. A higher die shear strength indicates superior adhesive strength.

[0172] (Curing condition 1) Using a UV irradiation device (NF-150 manufactured by Ushio Inc.), the illuminance was 33 mW / cm². 2 The resin composition was irradiated with ultraviolet light through a glass slide for 60 seconds (exposure dose 2000 mJ / cm²). 2 The adhesive strength of the cured product obtained by curing the resin composition under this curing condition 1 may hereafter be referred to as "adhesive strength 1".

[0173] (Adhesion strength 2) Using a UV irradiation device (NF-150 manufactured by Ushio Inc.), the illuminance was 33 mW / cm². 2 The resin composition was irradiated with ultraviolet light through a glass slide for 15 seconds (exposure dose: 500 mJ / cm²). 2 ). The adhesive strength of the cured product obtained by curing the resin composition under these curing conditions 2 may hereafter be referred to as "adhesive strength 2".

[0174] (Adhesion strength 3) Using a UV irradiation device (NF-150 manufactured by Ushio Inc.), the illuminance was 33 mW / cm². 2 The resin composition was irradiated with ultraviolet light for 3 seconds through a glass slide (exposure dose 100 mJ / cm²). 2 ). The adhesive strength of the cured product obtained by curing the resin composition under these curing conditions 3 may hereafter be referred to as "adhesive strength 3".

[0175] <Test 2. Viscosity Measurement Test> The viscosity of the resin composition was measured at 25°C using an E-type viscometer (RE-80U, manufactured by Toki Sangyo Co., Ltd., with a 1°34' × R24 cone).

[0176] <Test 3. Adhesion test between groove and optical fiber> A silicon chip with V-grooves formed thereon (manufactured by OZoptics, product name "VGC-8-250-10.4-3.8-1") was prepared. This chip had a length of 10.4 mm, a width of 3.8 mm, and a thickness of 1 mm, and eight V-grooves for installing optical fibers were formed at a pitch of 250 μm. Each V-groove had a width of 0.195±0.005 mm, a depth of 0.138±0.005 mm, a length of 5.3 mm, and the angle formed by the side surface of the V-groove with respect to the main surface of the chip was 54.74°.

[0177] An 8-channel single-mode ribbon fiber was placed on the silicon chip such that the tip of the optical fiber of the ribbon fiber rested on the V-grooves of the silicon chip. 20 mg of the resin composition was applied to the V-grooves using a dispenser. A V-groove chip lid (manufactured by OZoptics, product name "VGC-LID-5.38-1") was placed on the applied resin composition. Illuminance 33 mW / cm 2 Ultraviolet rays were irradiated through the V-groove chip lid to cure the resin composition. Immediately after the resin composition was cured, a 1 g weight was placed on the optical fiber. When the weight was placed, the case where the optical fiber did not peel off from the V-groove of the silicon chip was judged as "Pass", and the case where it peeled off was judged as "Fail".

[0178] The above operation was performed with the ultraviolet irradiation time set to 60 seconds (exposure amount 2000 mJ / cm 2 ), 15 seconds (exposure amount 500 mJ / cm 2 ) and 3 seconds (exposure amount 100 mJ / cm 2 ) respectively, and a pass or fail judgment was made. From the judgment results, the exposure amount required to adhere the optical fiber to the V-groove of the silicon chip was evaluated according to the following criteria. "Excellent": Pass at an exposure amount of 100 mJ / cm 2 or more "Good": Pass at an exposure amount of 500 mJ / cm 2 or more "Fair": Pass at an exposure amount of 2000 mJ / cm 2 or more "Poor": Fail at an exposure amount of 2000 mJ / cm 2

[0179] <Test 4. Appearance Evaluation Test>​ In Test 3 above, the ultraviolet irradiation time was 60 seconds (exposure dose 2000 mJ / cm 2 ), the prepared sample was observed, and the appearance after bonding the V-groove and the optical fiber was evaluated according to the following criteria. "Excellent": The resin composition or its cured product does not overflow from the V-groove chip lid, and the optical fiber is bonded to the V-groove. "Fair": The resin composition or its cured product overflows from the V-groove chip lid, and the optical fiber is bonded to the V-groove. "Poor": The optical fiber cannot be bonded to the V-groove, and the V-groove and the optical fiber are peeled off.

[0180] <Test 5. Absorbance Measurement Test of Cured Product of Resin Composition> A 2 mm thick silicone rubber frame was placed on a release-treated polyethylene terephthalate film ("AL-5" manufactured by Lintec Corporation), and the resin composition was injected into the frame. A release-treated polyethylene terephthalate film ("AL-5" manufactured by Lintec Corporation) was placed thereon, and the resin composition was irradiated with ultraviolet light at an illuminance of 33 mW / cm using a UV irradiation apparatus ("NF-150" manufactured by Ushio Inc.) 2 for 60 seconds (exposure dose 2000 mJ / cm 2 ). The frame and the polyethylene terephthalate film were removed to obtain a cured product of the resin composition. In the thickness direction of the obtained cured product, the absorbance of the cured product was measured at a measurement wavelength of 1310 nm using a spectrophotometer ("V-770" manufactured by JASCO Corporation).

[0181] <Results> Hereinafter, the results of Examples and Comparative Examples are shown in the following table. In the table below, the abbreviations have the following meanings. "(A) Content rate": The amount of component (A) relative to 100 parts by mass of the total amount of components (A) to (C) "(B) Content rate": The amount of component (B) relative to 100 parts by mass of the total amount of components (A) to (C) "(C) Content rate": The amount of component (C) relative to 100 parts by mass of the total amount of components (A) to (C) "(D) Content rate": The amount of component (D) relative to 100 parts by mass of the total amount of components (A) to (C) "(F) Content": Amount of component (F) relative to 100 parts by mass of the total amount of components (A) to (C). "(E) Content": The amount of component (E) relative to 100% by mass of the total resin composition.

[0182] [Table 1]

[0183] [Table 2]

[0184] [Table 3]

[0185] [Table 4] [Explanation of Symbols]

[0186] 1 Optical devices 100 Silicon Chips Main surface of 100U silicon chip 110 Groove 110B Bottom of the groove 110E End of groove 110S Groove side 120 Optical waveguide 121 cores 122 Clad 200 optical fibers 300 Adhesive part 400 Lid material

Claims

1. A resin composition for bonding optical fibers to grooves in a silicon chip; The resin composition comprises (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator; The resin composition may or may not contain (E) inorganic particles; (E) The amount of inorganic particles is 15% by mass or less relative to 100% by mass of the total amount of the resin composition. The total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin is 95% by mass or more of the total amount of the resin composition (100% by mass). (C) A resin composition in which the amount of aliphatic liquid epoxy resin is less by mass than (A) an aliphatic liquid oxetane resin.

2. A resin composition for bonding optical fibers to grooves in a silicon chip; The resin composition comprises (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator; The resin composition may or may not contain (E) inorganic particles; (E) The amount of inorganic particles is 15% by mass or less relative to 100% by mass of the total amount of the resin composition. The total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin is 95% by mass or more of the total amount of the resin composition (100% by mass). (B) A resin composition comprising an aliphatic solid epoxy resin, which is an epoxy resin obtained by hydrogenating an aromatic ring-containing epoxy resin.

3. A resin composition for bonding optical fibers to grooves in a silicon chip; The resin composition comprises (A) an aliphatic liquid oxetane resin, (B) an aliphatic solid epoxy resin, (C) an aliphatic liquid epoxy resin, and (D) a photocationic polymerization initiator; The resin composition may or may not contain (E) inorganic particles; (E) The amount of inorganic particles is 15% by mass or less relative to 100% by mass of the total amount of the resin composition. The total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin is 95% by mass or more of the total amount of the resin composition (100% by mass). (C) A resin composition comprising an aliphatic liquid epoxy resin, which is an epoxy resin obtained by hydrogenating an aromatic ring-containing epoxy resin.

4. The resin composition according to any one of claims 1 to 3, wherein the amount of (A) aliphatic liquid oxetane resin is 10 parts by mass or more and 50 parts by mass or less, based on 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin.

5. The resin composition according to any one of claims 1 to 3, wherein the amount of (B) aliphatic solid epoxy resin is 40 parts by mass or more and 80 parts by mass or less with respect to 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin.

6. The resin composition according to any one of claims 1 to 3, wherein the amount of (C) aliphatic liquid epoxy resin is 1 part by mass or more and 30 parts by mass or less with respect to 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin.

7. (D) The resin composition according to any one of claims 1 to 3, wherein the amount of the photocationic polymerization initiator is 0.1 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the total amount of (A) aliphatic liquid oxetane resin, (B) aliphatic solid epoxy resin, and (C) aliphatic liquid epoxy resin.

8. (B) The resin composition according to any one of claims 1 to 3, wherein the aliphatic solid epoxy resin comprises one or more selected from the group consisting of hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a six-membered ring.

9. (C) The resin composition according to any one of claims 1 to 3, wherein the aliphatic liquid epoxy resin comprises one or more selected from the group consisting of hydrogenated bisphenol A type epoxy resin and aliphatic epoxy resin containing a six-membered ring.

10. (E) The resin composition according to any one of claims 1 to 3, wherein the amount of inorganic particles is 0.1% by mass or less with respect to 100% by mass of the total amount of the resin composition.

11. The resin composition according to any one of claims 1 to 3, wherein the mass ratio of (A) aliphatic liquid oxetane resin to (C) aliphatic liquid epoxy resin ((C) aliphatic liquid epoxy resin / (A) aliphatic liquid oxetane resin) is 0.01 or more and 0.9 or less.

12. The process of installing optical fibers in the grooves of the silicon chip, A step of applying the resin composition according to any one of claims 1 to 3 to the groove, A process for curing the resin composition, A method for manufacturing a device, including

13. A silicon tip with grooves formed on it, Optical fibers placed in the grooves of the silicon chip, It comprises an adhesive portion for bonding the optical fiber to the groove; A device in which the adhesive portion includes a cured product of the resin composition described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Adhesive composition and optical semiconductor device

    JP2022069039A